Thermographic real-time-monitoring of surgical radiofrequency and microwave ablation in a perfused porcine liver model - Primavesi, Florian (Oncol Lett, 2018)
Radiofrequency ablation (RFA) and microwave ablation (MWA) are currently the dominant modalities to treat unresectable liver tumors. Monitoring the ablation process with b-mode-sonography is often hampered by artefacts. Furthermore, vessels may cause cooling in the adjacent tumor target (heat-sink-effect) with risk of local recurrence. The present study evaluated infrared-thermography to monitor surgical RFA/MWA and detect heat-sink-effects in real-time. RFA and MWA of perfused porcine livers was conducted at peripheral and central-vessel-adjacent locations, and monitored by real-time thermography. Ablation was measured and evaluated by gross pathology. The mean time for ablation was significantly longer in RFA compared with MWA (8 vs. 2 min). Although mean macroscopic ablation diameter was similar (RFA, 3.17 cm; MWA, 3.38 cm), RFA showed a significant heat-sink-effect compared with MWA. The surface temperature during central RFA near vessels was 1/3 lower compared with peripheral RFA (47.11±8.35°C vs. 68.72±12.70°C; P<0.001). There was no significant difference in MWA (50.52±8.35°C vs. 50.18±10.35°C; P=0.74). In conclusion, thermography is suitable to monitor the correct ablation with MWA and RFA. The results of the current study demonstrated a significant heat-sink-effect for RFA, but not MWA near vessels. MWA reaches consistent surface temperatures much faster than RFA. With further in vivo validation, thermography may be useful to ensure appropriate ablation particularly near vulnerable or vascular structures.